Detection of Diffuse Hot Gas around the Young, Potential Superstar Cluster H72.97–69.39 - Trinity L. Webb; Jennifer A. Rodriguez; Laura A. Lopez; Anna L. Rosen; Lachlan Lancaster; Omnarayani Nayak; Anna F. McLeod; Paarmita Pandey; Grace M. Olivier (The Astrophysical Journal)
We present the first Chandra X-ray observations of H72.97–69.39, a highly embedded, potential superstar cluster in its infancy located in the star-forming complex N79 of the Large Magellanic Cloud. We detect particularly hard, diffuse X-ray emission that is coincident with the young stellar objects identified with JWST, and the hot gas fills cavities in the dense gas mapped by the Atacama Large Millimeter/submillimeter Array. The X-ray spectra are best fit with either a thermal plasma or power-law model, and assuming the former, we show that the X-ray luminosity of L _X = (1.0 ± 0.3) × 10 ^34 erg s ^−1 is a factor of ∼20 below the expectation for a fully confined wind bubble. Our results suggest that stellar wind feedback produces diffuse hot gas in the earliest stages of massive star cluster formation and that wind energy can be lost quickly via either turbulent mixing followed by radiative cooling or by physical leakage.